Pengaruh Cita Rasa Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Gelato (Studi Kasus Pelanggan Ilvero) - Atmaja, Sena; Perwithasari, Resy; Hadi, Helmas Septiyo; Rosidawaty, Rosidawaty (Universitas Muhammadiyah Tangerang, 2024)
The purpose of this study is to determine and analyze the influence of Taste and Service Quality on Purchase Decisions both partially and simultaneously. The sample consists of 96 respondents who are customers of Il Vero. This research uses a quantitative method. The sampling technique used is purposive sampling. Data was collected using a questionnaire instrument with a Likert Summated Rating (LSR) scale, with evaluation criteria ranging from strongly disagree to strongly agree. The data analysis method was processed using SPSS version 26. The partial results of the study show that Taste (X1) has a positive and significant effect on Purchase Decisions (Y) with a t-value of 4.878, a t-table value of 1.984, and a significance value of 0.000 < 0.05. Service Quality (X2) also has a positive and significant effect on Purchase Decisions (Y) with a t-value of 3.563, a t-table value of 2.30, and a significance value of 0.001 < 0.05. Simultaneously, Taste (X1) and Service Quality (X2) have a positive and significant effect on Purchase Decisions (Y) with a t-value of 110.347, a t-table value of 2.30, and a significance value of 0.004 < 0.05. The regression equation results indicate that Taste has the highest influence, followed by Service Quality, which has the smallest influence.